SISTEM PENENTU KEPUTUSAN KELAS UNGGULAN DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Siti Rofi’ah; Firman Santoso; Adi Susanto (LPPM Universitas Abdurrab, 2025)
The use of information technology in education is an important need to improve efficiency and objectivity, especially in the student placement process. MTs Salafiyah Safi'iyah Sukorejo Putri faces challenges in determining students for superior classes conventionally, which are prone to errors, less transparent, and time-consuming. This study aims to develop a decision support system (DSS) based on the Simple Additive Weighting (SAW) method to assist the student selection process based on certain criteria, namely the value of reading the Qur'an, reading the book, and the average report card score. The study was conducted by collecting data through observation, interviews, and documentation. The system development method uses the Agile Development approach to ensure flexibility in responding to changing user needs. The system works by normalizing data, weighting criteria according to priority levels, and ranking to produce a list of students who are eligible to enter superior classes. The priority subject-based tiebreaker feature is used to resolve cases of students with the same final score. The implementation results show that this system is able to increase the efficiency of the selection process by up to 40% compared to manual methods. The system also improves the accuracy of data processing through automatic validation, so that the selection results are more objective and accountable. With this system, MTs Salafiyah Safi’iyah Sukorejo Putri can place students based on their potential more fairly and systematically. In conclusion, the implementation of the SAW-based system not only supports a more transparent and efficient selection process but also helps educational institutions design targeted curricula for superior students.